The Experience of Resilience of Chronic Renal Failure Patients with Haemodialysis Therapy: a Qualitative Study - Patricia Yunita Dwi Ariyani; Chatarina Hatri Istiarini (Faculty of Nursing, Universitas Jember, 2022)
Background: Chronic Kidney Failure patients who have routinely followed haemodialysis therapy have to experience resilience, being able to adapt, survive, and improve their quality of life even though their life is dependent on haemodialysis. Purpose: Objectives to know the experience of the resilience of chronic kidney failure patients with haemodialysis therapy at Hospital, in Yogyakarta Indonesia 2020. Methods: It was qualitative with a phenomenology approach. The sample was 5 people taken with the purposive sampling technique. Data was collected with in-depth interview retrieval via video call with a cell phone as a voice recording device. Content analysis was used with the type of conversation analysis. Results: The result of the interview obtains 7 themes, namely experience to remain calm, the experience of controlling impulses, having positive expectations, focusing on problems and solving problems, having positive social relationships, belief and trust to achieve problem-solving, and able to achieve positive values in life. Conclusion: In this research, it shows that the participant response is good. The resilience possessed by five participants is good and in accordance with the source of formation/basic resilience ability, as evidenced by the 7 themes raised. Other researchers are advised to develop this research related to experiences of resilience based on the stages of resilience experienced by patients with chronic kidney failure with haemodialysis therapy. Keywords: Resilience; Chronic Kidney Failure Patients; Haemodialysis (HD)